The Cultivation of Marketing Students’ Innovation Ability From the Perspective of Cybernetics - Wang, Yongqiang (Journal of Theory and Practice of Contemporary Education, 2024)
Under the new situation, in the society of knowledge economy, it is not only the competition of talent quantity, but also the competition of talent innovation ability. In order to adapt to the development path of the Times, marketing specialty should start from the talent training system, rationally use cybernetics, and maintain the appropriate transformation and sustainable development of the specialty. In this way, not only to improve students' practical ability, but also to improve their innovation ability, and lay a good foundation for future development.